Does Hyperbaric Oxygen Administration Before or After Irradiation Decrease Side Effects of Irradiation on Implant Sites? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Background: One of the main limitations of implant-based breast reconstruction is the high rate of complications such as capsular contracture and poor aesthetic outcome, due to adjuvant radiotherapy. Hyperbaric oxygen treatment (HBOT) has been used to assist wound healing in the prevention and treatment of the side effects of irradiation. We aimed to investigate this effect of HBOT on the capsule reaction and skin, applied before and after irradiation, following the placement of an implant under the dorsal skin of the rat. Methods: Fifteen Wistar rats were randomly divided into 3 groups. A 18-mL smooth testicular implant was introduced into a subcutaneous pocket located on the dorsum of each rat. A single dose of 17-Gy irradiation was given to the implanted area of each rat at the third week. HBOT which lasted 3 weeks was administered to group I before irradiation, group II after irradiation. The control group did not receive HBOT. All of the rats were killed at the ninth week (6 weeks after irradiation). The dorsal skin with the capsule overlying the implant were excised for histopathological processing. The thickness of the capsule reaction of each group was evaluated statistically. Results: Our histopathological examination revealed changes due to radiation in the control group. Many of these findings were found to be more subtle in group I and nearly absent in the group II. There was not any statistical difference between the thickness of the capsule reactions of the control group and group I, or group I and group II, but the capsular thickness of the control group was statistically higher than group II. Conclusion: It can be predicted that the use of HBOT following irradiation is an effective tool to reduce the capsule reaction of the implanted area and the tissue damage seen in radiodermatitis.
Keywords: hyperbaric oxygen treatment; irradiation; implant; capsule; IMMEDIATE BREAST RECONSTRUCTION; RADIATION-THERAPY; TISSUE EXPANDERS; COMPLICATIONS; RADIOTHERAPY; MASTECTOMY; CANCER; SKIN; OSTEORADIONECROSIS; SATISFACTION